Free-energy barrier at droplet condensation - Nuβbaumer, Andreas; Bittner, Elmar; Janke, Wolfhard (Progress of theoretical physics. Supplement, 2010)
We discuss several aspects of a Monte Carlo computer simulation study of the condensation of macroscopic droplets emerging in the two-dimensional Ising lattice-gas model. By varying the particle density at fixed temperature we monitor the droplet formation in detail and compare our results with recent analytical predictions in the infinite-volume limit. Three different lattice discretizations are considered which are found to yield very similar results when presented in properly scaled variables. Particular emphasis is placed on the free-energy barrier associated with droplet formation and its implication for multimagnetical simulations.